PERAN BASOFIL DALAM IMUNITAS TERHADAP CACING - Jatmiko, Safari Wahyu (Biomedika, 2012)
Basophils are polymorphonuclear leukocytes that play an important role in immunity. Basophils can be activated by antibodies and other molecules. Basophils are able to recognize antigens of worms and give some responses. Basophils involvement in immunity againt worms are played by migratingto the worm infected tissue, trigger eosinophilia and eosinophil migration into the tissue, activating mast cells, triggering the formation of AAM, directing Th cell polarization toward Th2 cells, and triggers immunoglobulin class switching to produce IgE.Keywords:Basophil, Helminthiasis